The Cost-Benefit Analysis of Brain Drain and Remittances: Identifying Strategic Priorities for Afghanistan’s Economic Development (Salam International Academic Journal, 2025)
This study investigates the cost-benefit dynamics of brain drain and remittances in Afghanistan, focusing on their socio-economic impacts and strategic implications for sustainable development. Employing a mixed-methods approach, the research integrates qualitative thematic analysis and quantitative regression models to examine the relationship between skilled migration, remittances, and overall economic performance, including GDP and human capital development. Data were sourced from international reports, academic studies, and global databases, capturing a comprehensive view of migration and remittance trends.The findings reveal that political instability, restrictive policies, and limited professional opportunities are major drivers of brain drain, undermining Afghanistan’s economic resilience and growth. While remittances positively contribute to GDP and poverty alleviation, over-reliance on these inflows creates long-term economic vulnerabilities. The study emphasizes the importance of governance reforms, strategies to retain skilled professionals, and policies to channel remittances into productive investments. These findings provide actionable insights for addressing brain drain while leveraging remittances for Afghanistan’s sustainable development.
Keywords: Brain drain; Remittances; Skilled migration; Afghanistan; Economic development; Political instability; Human capital; Governance reforms; Sustainable development; Socio-economic challenges